COMPARATIVE EVALUATION OF SHEAR BOND STREANGTH OF SEVENTH GENERATION ADHESIVE SYSTEM TO WMTA AND BIODENTINE: AN IN VITRO STUDY - Mali, Sneha R.; Mangala, T.M.; Phase, Abhijeet; Mahaparale, Rushikesh; Saraf, Adish; Pawar, Sagar (International Journal of Psychosocial Rehabilitation, 2020)
Aim: This study aimed for similar assessment of shear bond quality of seventh generation bonding system with MTA and Biodentine. Materials and Methods: 80 acrylic blocks with central hole of 4mm diameter & 2mm height were prepared. 40 acrylic cylindrical blocks were completely loaded up with MTA (Group 1) & another 40 with Biodentine (Group2). Samples were put away for 72 hours at 37°C with 100% humidity. Samples from each group were randomly divided into different 2 groups of 20 each Group 1A: MTA WITH BONDING AGENT ;Group 1B: MTA WITHOUT BONDING AGENT (control);Group 2A: BIODENTINE WITH BONDING AGENT; Group 2B: BIODENTINE WITHOUT BONDING AGENT (control).A composite material (Clearfil Mejesty) applied into plastic matrix of cylindrical shaped with an internal diameter of 2mm and height of 2 mm. light-emitting diode light-curing unit was used with an intensity of 1,200mV/cm2 for 20 seconds for Light curing. The polymerized samples were put away for 24 hours in 100% relative humidity at 37°C. In universal testing machine samples were made sure about in a holder set on the platen at that point sheared with a blade edge sharp edge At Cross head speed: 1 mm/minute. Examination of fractured samples test were done under a stereomicroscope. Analysis of obtained Data were done Results: At the point when shear bond qualities of adhesive system were analyzed, no noteworthy contrasts were found between both control groups. (p > .05).the bond strength of group 2A introduced altogether higher bond quality values (48.15 MPa) than group 1A (28.51Mpa) (p < .05). Most of the observed modes of failure were cohesive than that of adhesive in both group 1A and 2A.Comparatively Cohesive fractures were more seen in Biodentin than that of MTA.Group 1B and group 2B(control groups) showed more adhesive failure compare to cohesive and mixed.